Constellation-based classification of avian reovirus in turkeys reveals shared virus origins among different meat-type farms - Hsueh, Cheng-Shun; Zeller, Michael; Hashish, Amro; Fasina, Olufemi; Piñeyro, Pablo; Aminu, Oluwatobiloba; El-Gazzar, Mohamed; Sato, Yuko (Frontiers in Veterinary Science, 2025)
The US poultry industry suffers significant economic losses due to Avian Reovirus (ARV) infections, which mainly cause arthritis/tenosynovitis in turkeys and chickens. The emergence of outbreaks since 2012 highlights the urgent need for improved epidemiological tools. Given the distinct evolutionary history of each segment of the virus and limited resolution of existing typing methods for ARV based on a single gene, a novel genotyping scheme was developed utilizing a constellation-based genotyping approach to enhance source tracing and control strategies especially for ARV in turkeys. A dataset of 199 ARV sequences from turkey hosts was curated and organized based on branch distances from maximum likelihood phylogenetic trees using TreeCluster. The grouping performance was evaluated and optimized according to established criteria described in this study. The proposed methods selected the M2, S1 σC-encoding region, and L3 genomic segments due to their non-random reassortment and biological significance. The novel scheme identified 8 major genotypes and revealed clear epidemiological links between turkey breeder and meat-type farms, as well as common shared sources among different meat-type farms, suggesting both vertical and horizontal transmission pathways. Additionally, reassortment events were detected using our novel typing scheme, highlighting the complex evolutionary dynamics of ARV. By correlating genotypic patterns with epidemiological data, this study provides a foundation for improved ARV monitoring and disease management.